An Exploration to Age-old Wisdom – A Book Review on Geriatrics in Ayurveda - Priya, N K; Binitha, A; Jigeesh, P P (International Research Journal of Ayurveda & Yoga, 2024)
“Geriatrics in Ayurveda” is authored by experts from both the fields of Ayurveda and modern medicine, seamlessly blending anecdotes from both medical systems. Geriatrics is Emerging as a challenging speciality, because of ever growing population of Aged people all over the world including India. In near Future, Every physician has to “treat’ a large Number of Aging Problems of our Ripe and Senior citizens in their CLINICS. Ayurveda system of Medicine (ASM) offers an Excellent Line of Management for these i.e. Aging problems under Rasayana and ‘Rasa’ therapies. In fact ‘Jara’ is an exclusive therapy for old-age related complaints. Keeping all these concepts in view, a systematic search to gather the relevant and useful information on “Geriatrics in Ayurveda” has been attempted along with inputs from (MODERN) Geriatrics, so as to have a comprehensive book on GERITRICS with Practical and clinical applications.The presented book was studied, analyzed, and compared with other contemporary works on a similar subject.